DOI: 10.22215/etd/2015-11015
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Flexibilities: Preschoolers' Developing Consecutive and Concurrent Cognitive Flexibility Skills

Abstract: Cognitive flexibility is the ability to think of something in more than one way. Research examining cognitive flexibility in 3-to 5-year-olds typically focuses on consecutive cognitive flexibility-the ability to consider several dimensions of a single stimulus one after another (e.g., sorting cards depicting blue boats and red rabbits by colour and then by shape). However, relatively little research examines preschoolers' concurrent cognitive flexibility skills-their ability to coordinate several dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(396 reference statements)
0
1
0
Order By: Relevance
“…The experimenter demonstrated the action (or lack of action) in a demonstration trial in which they showed children what they should do if they heard, "Simon says touch your knees", and if they just heard, "Touch your knees". Children Dimensional Change Card Sort (DCCS; modified from Zelazo, 2006, as in Prodjarny, 2015See Appendix S). In this task, children were shown cards that varied along two dimensions, colour and shape (e.g., red rabbits and blue boats) and were instructed to sort them into two boxes.…”
Section: Methodsmentioning
confidence: 99%
“…The experimenter demonstrated the action (or lack of action) in a demonstration trial in which they showed children what they should do if they heard, "Simon says touch your knees", and if they just heard, "Touch your knees". Children Dimensional Change Card Sort (DCCS; modified from Zelazo, 2006, as in Prodjarny, 2015See Appendix S). In this task, children were shown cards that varied along two dimensions, colour and shape (e.g., red rabbits and blue boats) and were instructed to sort them into two boxes.…”
Section: Methodsmentioning
confidence: 99%